The Curt Flood story the man behind the myth - Weiss, Stuart L.; ebrary, Inc. (Columbia : University of Missouri Press, 2007)
"Examines Curt Flood's often troubled personal life and explores his possible motives for suing Major League Baseball in 1970. For challenging baseball's reserve system, which he likened to bondage, the St. Louis Cardinals center fielder in time was lionized. But this recognition came at great personal expense"--Provided by publisher.
It takes a village -- Alone among the peckerwoods -- A minor in the majors -- The (almost) golden years -- A gold glove is tarnished -- The ultimatum -- The trade -- Trials and tribulations -- Second chance -- Last act.
Includes bibliographical references (p. 237-246) and index.
Electronic reproduction.
Keywords: Flood, Curt, -- 1938-1997.; African American baseball players -- Biography; Baseball players -- United States -- Biography; Electronic books